Healthcare Service Utilization by Patients with Obstructive Sleep Apnea: A Population-Based Study - Kao, Li-Ting (PLoS One, 2015)
OBJECTIVE: Although obstructive sleep apnea (OSA) is not a life-threatening disease, very few studies have compared differences in healthcare service utilization between patients with and those without OSA in an Asian population according to different age groups. This study attempted to investigate differences in healthcare service utilization between patients with and those without OSA in different age groups in Taiwan. METHODS: Sampled subjects and data on their health service utilization were retrieved from the Taiwan Longitudinal Health Insurance Database 2005. We included 568 patients with OSA and 2840 subjects without OSA. Each subject was followed for a 1-year period to evaluate their healthcare resource utilization. Wilcoxon-Mann-Whitney tests were performed to compare differences in healthcare utilization between patients with and those without OSA during the 1-year follow-up period. RESULTS: As to all healthcare service utilization, patients with OSA had significantly more outpatient visits (30.3 vs. 18.6), outpatient costs (US$1231.2 vs. US$764.8), inpatient days (1.8 vs. 1.2), inpatient costs (US$563.6 vs. US$276.7), and total costs (US$1794.8 vs. US$1041.5) than comparison subjects during the 1-year follow-up period. Moreover, patients with OSA aged 40~49 and 50~59 years respectively incurred 2.11- and 2.02-fold higher total costs compared to patients without OSA. However, patients with OSA aged over 70 years did not have higher total costs compared to those without OSA. CONCLUSIONS: This study found that patients with OSA had greater healthcare service utilization than those without OSA. Additionally, patients with OSA in the 40~49- and 50~59-year age groups had about 2-fold higher total costs of healthcare services than those without OSA.